Optical profiling of macrophages - Speight, Tom (The University of Edinburgh, 2020)
Macrophages are required to show plasticity in how they react to their microenvironment and orchestrate an inflammatory response. With such an integral role in human immunity, aberrant macrophage function can directly contribute to a variety of pathologies: from driving chronic inflammation to a compromised clearance of invading pathogens. Although there are pharmaceutical opportunities to restore alveolar macrophage function in disease, there still remains a challenge to truly profile their activity in situ. The use of optical endomicroscopy - a non-invasive, fibre-optic imaging platform capable of accessing the alveolar space, may be used in combination with optical probes to profile alveolar macrophage activity in their native environment. Work outlined in this thesis covers the characterisation of a human monocytederived macrophage model phenotype, performed using gold-standard in vitro systems including flow cytometric analysis of receptor expression and phagocytic activity. The work then moves on to explore alternative ways of optically profiling macrophages that may have clinical applications. An optical probe was synthesised to target the mannose receptor, a cell-surface receptor expressed on macrophages, using a camelid nanobody fragment as a targeting ligand. Initial characterisation showed cell-type specificity of the probe towards macrophages. While labelling appeared to be via active internalisation by cells, more evidence is required to determine if this probe interacts specifically with the mannose receptor target. A novel form of optical endomicroscopy was used to explore imaging macrophages, label-free, via their auto-fluorescent emission spectra. This was to distinguish macrophages following internalisation of a fluorescent target, without further labelling required to image negative cells. Initial imaging showed that in vitro monocyte-derived macrophages did not fluoresce brightly enough to be imaged label-free, though it is expected that primary lung macrophages – particularly from COPD patients who smoke – would be sufficiently bright enough to profile with this technique. Ultimately this work will be the foundation to profiling primary alveolar macrophages in health and disease. Using optical endomicroscopic imaging systems with optical probes for markers of cell phenotype, as well as other label-free methods in development, there is potential to profile the activity of alveolar macrophages directly in the alveolar space of the human lung and monitor pharmaceutical effects on their activity.
Keywords: macrophage immune cells; fluorescent antibody fragment; binding markers; macrophages; macrophage mannose receptor; optical endomicroscopy; auto-fluorescent emission spectra